Fabrication and Photovoltaic Conversion Performances of Imidazolyl and Fumaric Acid Composite Langmuir–Blodgett Membranes - Bian, Pengfei; Yang, Huiqing; Zhang, Lexin; Liu, Zhiwei; Qiao, Guiying; Han, Yong; Jiao, Tifeng (Langmuir, 2024)
Novel organic small molecule structures have received increasing attention in the preparation of multifunctional thin film materials and have become the subject of research in many cutting-edge directions. In this work, imidazolyl and transbutylene glycolic acid molecules and dye molecules were designed and prepared as composite films by supramolecular self-assembly in the LB technique, and their morphological features and spectral properties were analyzed. The results showed that the prepared LB films presented different aggregation states. In addition, their photoelectrochemical properties, on ITO sheets were tested, all of which showed good optoelectronic properties, and their binding energies, structure optimization, and electrostatic potentials were theoretically calculated by DFT simulations, which proved that the prepared films have good optoelectronic properties, and have the potential to become optoelectronic multifunctional ultrathin film devices.